2022
DOI: 10.3390/cells12010082
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification Cytochrome P450s (CYPs) in Families 1–3 Produce Functional Oxylipins from Polyunsaturated Fatty Acids

Abstract: This manuscript reviews the CYP-mediated production of oxylipins and the current known function of these diverse set of oxylipins with emphasis on the detoxification CYPs in families 1–3. Our knowledge of oxylipin function has greatly increased over the past 3–7 years with new theories on stability and function. This includes a significant amount of new information on oxylipins produced from linoleic acid (LA) and the omega-3 PUFA-derived oxylipins such as α-linolenic acid (ALA), docosahexaenoic acid (DHA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 209 publications
0
9
0
Order By: Relevance
“…Reductions in CYP-derived oxylipins are consistent with inflammatory conditions [ 35 , 36 ]. All of the other oxylipin metabolites that were inversely associated (reduced in concentration) with increasing PFOS concentrations were epoxides, suggesting that epoxide hydrolase activity was induced by PFOS treatment in the females and, in turn, dihydroxy-oxylipins were produced [ 12 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reductions in CYP-derived oxylipins are consistent with inflammatory conditions [ 35 , 36 ]. All of the other oxylipin metabolites that were inversely associated (reduced in concentration) with increasing PFOS concentrations were epoxides, suggesting that epoxide hydrolase activity was induced by PFOS treatment in the females and, in turn, dihydroxy-oxylipins were produced [ 12 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, 19,20-EpDPA is decreased possibly due to the induction of epoxide hydrolases, and is lower in 1-PFOS-treated hCYP2B6-Tg that show less steatosis than Cyp2b-null mice ( Figure 2 ). Previous research has shown that 19,20-EpDPA is inversely associated with hepatocyte lipid accumulation [ 12 , 77 ]. 9,10-DiHOME, which was induced by PFOS, stimulates adipogenesis through PPARγ [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxylipin generation is a highly controlled process that is sensitive to both nutrition- and exercise-based interventions [ 51 , 52 ]. More than 50 enzymes are involved in producing oxylipins, and signaling is conducted by binding to a variety of receptors or by interacting with intracellular pathways [ 52 , 53 , 54 ]. The enzymes that regulate oxylipin production and the receptors to which they bind are potential targets for metabolites derived from dietary macronutrients and polyphenols [ 9 , 10 , 11 , 12 , 13 , 14 , 54 ].…”
Section: Discussionmentioning
confidence: 99%